Conscience as a Regulatory Function: An Integrative Theory Put to the Test - Verkade, Marion (International journal of offender therapy and comparative criminology, 2020)
The subject of this study is an integrative theory of the conscience. According to this theory, conscience is operationalised as a regulatory function of one's own behaviour and identity, resulting from an interplay of empathy, self-conscious emotions such as guilt and shame, and moral reasoning. This study aimed to evaluate conscience in an adult forensic psychiatric sample by assessing the underlying factors proposed by Schalkwijk. Offenders (n = 48) appeared to show less affective but not less cognitive empathy, less identification with others, less personal distress in seeing others' suffering, less shame and shame-proneness, and lower levels of moral reasoning than non-offenders (n = 50). In coping with self-conscious emotions, offenders used the same amount of externalising coping strategies, but fewer internalising coping strategies.